A Brief Overview of Measuring the Effects of Managers' Training, Communication and Motivation and their Impact on Managerial Performance in Health and Hotel Tourism in Kosovo.Case study: Managere’s of Centrer of Thermal Tourism and Five Stars Hotel in Kos: Array - Kovaçi, Idriz; Tahiri, Alberta; Mehmeti, Ismail; Thaqi, Agim (Acta Universitatis Danubius. Œconomica, 2020)
The effects of training, human resource communication, and motivation of managers are shown to be statistically significant factors affecting managerial performance in health and hotel tourism in KosovoThe findings, which have been gathered by tourism and hotel sector managers, show that training, communication and motivation have a positive impact on the performance of managers. ( p value = .000 ) which gives us the understanding that we need to continuously support trainings with managers, have a professional approach with human resources and be motivated. Also, organized trainings and proper communication with human resources, have a positive impact on enhancing the performance of managers in thermal and hotel centers in Kosovo. ( p value=.000 ). We say that the Hotest and Health Tourism sector are two sectors that are positively impacting on economic and social development in Kosovo and this provides opportunities for employment and professionalism in these sectors.